Ethnomathematics in Serampang XII Dance by Deli Malay Ethnic Group: An Exploration - Br Ginting, Siti Salamah; Hasibuan, Aulia Rahman (Unnes Journal of Mathematics Education, 2024)
This study aimed to explore mathematical concepts in the local culture known as ethnomathematics. The culture examined in this study is the Serampang XII Dance performance, originating from the Deli Malay ethnic group in the province of North Sumatra. This qualitative descriptive research adopts an ethnographic approach, revealing and describing local cultural facts discovered in the field. It is revealed that the Serampang XII Dance performance incorporates various applications of mathematical concepts, including basic counting, geometric angle concepts, geometric transformation concepts, set concepts, relation concepts, and flat shape concepts. This research aims to provide answers to its main question, which is, "What mathematical concepts can be identified and further explored in the Serampang XII Dance performance?". In conclusion, Serampang XII Dance can be considered an ethnomathematical innovation that can be used as a foundation for a new mathematics teaching approach with the hope of transforming the perception of mathematics education from monotony to enjoyment.